Transmission of Ultrasonic Waves Via Optical Silica Glass Fiber Doped by 7.5% of TiO2 with the Use of Power Sandwich Transducer - MUC, Sylwia; GUDRA, Tadeusz (Archives of Acoustics, 2011)
The possibility of acoustic wave propagation in optical waveguides creates newprospects for simultaneous transmission of laser beams and ultrasonic waves. Combinedlaser-ultrasonic technology could be useful in e.g. surgical treatment. The articlepresents the results of experimental studies of transmission of ultrasonic wavein optical fibres, the core of which is doped by 7.5% of TiO2, using a sandwichtypetransducer. It also presents amplitude characteristics of an ultrasonic signalpropagated in the optical fibre. Authors studied the effect which the length of thefibre has on the achieved output signal amplitudes. They presented the relation ofthe output signal amplitude from a capacitive sensor to the power applied to thesandwich-type transducer. The obtained results were compared with the results producedwhen using an optical fibre with a core doped by 3% of GeO2, in order toselect optical fibre suitable for simultaneous transmission of ultrasonic waves andlaser rays.